A prospective study of complications in newly diagnosed type 2 diabetes mellitus patients of lower socioeconomic group with special reference to microvascular complication and metabolic syndrome - Anand, K. Satya; ., Ruksana; Acharya, Anand (International Journal of Research in Medical Sciences, 2019)
Background: All these metabolic derangements exist for many years in the asymptomatic phase of type 2 diabetes and they predispose to development of complications even before clinical diagnosis. Metabolic syndrome is considered to be a precursor of type 2 diabetes. Present study is primarily aimed to study the prevalence of micro vascular complications and metabolic syndrome in newly diagnosed type 2 diabetes mellitus patients of low socio-economic group. Methods: This is a cross sectional prospective study conducted in the dept. of general medicine Konaseema institute of medical science Amalapuram, Andhra Pradesh, India from November 2016 to October 2018. Based on exclusion and inclusion criteria 103 patients were enrolled for this study. Various parameters like age, sex, body mass index, waist circumference, lipid profile, systolic and diastolic blood pressure, neuropathy, nephropathy and retinopathy was measured. Results: The mean age of the patient was 48±10.0 years. Fasting and 2 hours OGTT was 174.6±46.8 mg/dl and 255.6±75.6 mg/dl. The mean of total cholesterol was 204.7±41.9 (mg/dl), Triglycerides was 218±83.4 (mg/dl) and HDL was 44±5.3 (mg/dl). Symptomatic neuropathy constituted 35.6% in 51-60 age group and 27.1% in 31-40 and 41-50 age groups. Objective neuropathy constituted highest (36.6%) in 51-60 age group. Retinopathy constituted highest (60%) in 51-60 age group and nephropathy constituted 26.3 % in 21-30 and 51-60 age groups. Conclusions: Prevalence of microvascular complications in newly diagnosed diabetics of low socioeconomic group were as follows: symptomatic neuropathy-57.3%, objective neuropathy-39.8%, retinopathy-4.9%, nephropathy-18.4%. These were similar to published studies from general population from the same geographical area.